Análise do polimorfismo nos genes CYP19a e CYP19b em Oreochromis niloticus da linhagem Supreme e suas relações com caracteres reprodutivos. - Rodrigues, Marília Danyelle Nunes (2011)
The aromatase enzyme complex is responsible for converting androgens into estrogens in vertebrates. One of the key enzymes of this complex is the cytochrome P450arom gene expression and regulation of this enzyme is directly linked to sexual differentiation. Estrogen is essential for the development of the gonads and various physiological processes, ranging from normal growth to reproductive behavior. This study aimed to correlate the polymorphisms in the genes CYP19a CYP19b. In a first moment with three strains used in aquaculture (Chitralada, Supreme and GIFT) using thirty animals of each strain and, a second time only with the Supreme strain which has also the objective of analyzing the sex ratios found in both treatments at different temperatures of water and to establish possible relationships between them, analyzing the 122 animals treated at 25 ° C and 129 animals of treatment at 35 ° C. After extraction of DNA samples were subjected to PCR using primers designed to flank a region of interest. After confirmation of amplification samples were subjected to electrophoresis on Origins apparatus for identification of alleles. In the first study was identified that there is a polymorphism in the promoter region of CYP19b in the three strains. Were observed three alleles, ranging from 141 to 123 bp. Thus the primers for amplification of microsatellites in the regulatory region of the gene CYP19b were efficient, and therefore its use for identification of mutations in this region can be employed in the typical analysis of microsatellites. In the second study was identified that there is a polymorphism in the regulatory region of the gene 10 CYP19a, 5 alleles were observed. The proportion of females and males found in the treatment at 25 ° C was 1:2,3 1:2,88 and treatment at 35 ° C. However, it can be assumed that the polymorphism present in this portion of the regulatory region may be related to sex reversal found. Whereas the attempt to select individuals with polymorphisms in the regulatory region of the aromatase gene (and CYP19a CYP19b) is an essential study to evaluate the expression levels of both, so you can see how it is being expressed in individuals that will reverse or not , allowing for the reversal temperature with a higher proportion.